Ecodistribution, infection rates and host preference of tsetse flies in the sleeping sickness focus of Bonon, west-central Côte d’Ivoire - BERTE, DJAKARIDJA (African Entomology, 2025)
The sleeping sickness focus of Bonon was the last one still active at a low endemic level in Côte d’Ivoire. An entomological survey carried out in June 2015 during the rainy season using “Vavoua” traps guided subsequent control activities. Indeed, it improved knowledge of tsetse fly ecology. All the tsetse flies caught (i.e. 1909) belonged to the subspecies Glossina palpalis palpalis (Robineau-Desvoidy, 1830), the major vector of Human African Trypanosomiasis (HAT) in Côte d’Ivoire. In this paper, we looked at the relationship between the apparent density (AD, flies/trap/day) and biotopes. The AD significantly varied according to biotopes, with high density around villages. The trypanosomes overall infection rate (mature and immature) according to microscopic observation was 23.2%. When considering mature infections, the infection rate was 5.5 %. Polymerase chain reaction (PCR) analyses confirmed the presence of Trypanosoma brucei s.l. and Trypanosoma congolense “forest type”. Blood meals analysis using cytochrome b gene sequences revealed that tsetse flies fed on pigs. The edges of the villages seem to constitute preferred habitats for tsetse flies where they are protected from insecticide pressure in the fields, and where they can easily take bloodmeals from free-ranging pigs. The findings of this study provided a baseline in decision-making for subsequent vector control activities.